Chronic adriamycin treatment impairs CGRP-mediated functions of meningeal sensory nerves. (June 2018) - Deák, Éva; Rosta, Judit; Boros, Krisztina; Kis, Gyöngyi; Sántha, Péter; Messlinger, Karl; Jancsó, Gábor; Dux, Mária
Abstract: Adriamycin is a potent anthracycline-type antitumor agent, but it also exerts potentially serious side effects due to its cardiotoxic and neurotoxic propensity. Multiple impairments in sensory nerve functions have been recently reported in various rat models. The present experiments were initiated in an attempt to reveal adriamycin-induced changes in sensory effector functions of chemosensitive meningeal afferents. Meningeal blood flow was measured with laser Doppler flowmetry in the parietal dura mater of adult male Wistar rats. The dura mater was repeatedly stimulated by topical applications of capsaicin, a transient receptor potential vanilloid 1 (TRPV1) receptor agonist, or acrolein, a transient receptor potential ankyrin 1 (TRPA1) receptor agonist, which induce the release of calcitonin gene-related peptide (CGRP) from meningeal afferents. The blood flow increasing effects of CGRP, histamine, acetylcholine and forskolin were also measured. Capsaicin- and acrolein-induced CGRP release was measured with enzyme-linked immunoassay in an ex vivo dura mater preparation. TRPV1 content of trigeminal ganglia and TRPV1-, CGRP- and CGRP receptor component-immunoreactive structures were examined in dura mater samples obtained from control and adriamycin-treated rats. The vasodilator effects of capsaicin, acrolein and CGRP were significantly reduced in adriamycin-treated animals while histamine-, acetylcholine- and forskolin-induced vasodilatation were unaffected. Measurements of CGRP release in an ex vivo dura mater preparation revealed an altered dynamic upon repeated stimulations of TRPV1 and TRPA1 receptors. In whole-mount dura mater preparations immunohistochemistry revealed altered CGRP receptor component protein (RCP)-immunoreactivity in adriamycin-treated animals, while CGRP receptor activity modifying protein (RAMP1)-, TRPV1- and CGRP-immunostaining were left apparently unaltered. Adriamycin-treatment slightly reduced TRPV1 protein content of trigeminal ganglia. The present findings demonstrate that adriamycin-treatment alters the function of the trigeminovascular system leading to reduced meningeal sensory neurogenic vasodilatation that may affect the local regulatory and protective mechanisms of chemosensitive afferents leading to alterations in tissue integrity. Highlights: Adriamycin alters dynamic of CGRP release upon repeated activation of nociceptors. Adriamycin treatment reduces neurogenic sensory vasodilatation in meningeal arteries. CGRP receptor function is altered in dural blood vessels after adriamycin treatment. Adriamycin induces multiple but selective impairments of receptor functions.